Parallel corpora based translation resources extraction - Simões, Alberto (2007)
This paper describes NATools, a toolkit to process, analyze and extract translation resources from Parallel Corpora. It includes tools like a sentence-aligner, a probabilistic translation dictionaries extractor, word-aligner, a corpus server, a set of tools to query corpora and dictionaries, as well as a set of tools to extract bilingual resources.